![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a, 7x^3 + 5 ( x - y )^2 v- 7y^3
= 7 ( x^3 - y^3 ) + 5 ( x-y )^2
= 7 ( x - y )^3 + 5 ( x-y ) ^2
= [ 7 ( x- y ) + 5 ] ( x-y) ^2
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(\left(x^2-2xy+y^2\right).\left(x-y\right)\)
\(=\left(x-y\right)^2.\left(x-y\right)\)
\(=\left(x-y\right)^3\)
\(=x^3-3x^2y+3xy^2-y^3.\)
b) \(\left(30x^4y^3-25x^2y^3-4x^4y^4\right):5x^2y^2\)
\(=\left(30x^4y^3:5x^2y^2\right)-\left(25x^2y^3:5x^2y^2\right)-\left(4x^4y^4:5x^2y^2\right)\)
\(=6x^2y-5y-\frac{4}{5}x^2y^2.\)
Chúc bạn học tốt!
![](https://rs.olm.vn/images/avt/0.png?1311)
\(1.5x\left(x^2+2x-1\right)-3x^2\left(x-2\right)=5x^3+10x^2-5x-3x^3+6x^2\)
\(=2x^3+16x^2-5x\)
\(=\left(2x^3-x\right)+\left(16x^2-4x\right)\)
\(=x\left(2x^2-1\right)+4x\left(4x-1\right)\left(ĐCCM\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(4x^4-21x^2y^2+y^4=\left(4x^4+4x^2y^2+y^4\right)-25x^2y^2\)
\(=\left(2x^2+y^2\right)^2-\left(5xy\right)^2=\left(2x^2-5xy+y^2\right)\left(2x^2+5xy+y^2\right)\)
b) \(x^5-5x^3+4x=x\left(x^4-5x^2+4\right)=x\left[\left(x^4-4x^2\right)-\left(x^2-4\right)\right]\)
\(=x\left[x^2\left(x^2-4\right)-\left(x^2-4\right)\right]=x\left(x^2-1\right)\left(x^2-4\right)\)
\(=x\left(x-1\right)\left(x+1\right)\left(x-2\right)\left(x+2\right)\)
c ) \(x^3+5x^2+3x-9=\left(x^3-x^2\right)+\left(6x^2-6x\right)+\left(9x-9\right)\)
\(=x^2\left(x-1\right)+6x\left(x-1\right)+9\left(x-1\right)\)
\(=\left(x^2+6x+9\right)\left(x-1\right)=\left(x+3\right)^2\left(x-1\right)\)
d ) \(x^{16}+x^8-2=x^{16}-x^8+2x^8-2=x^8\left(x^8-1\right)+2\left(x^8-1\right)\)
\(=\left(x^8+2\right)\left(x^8-1\right)=\left(x^8+2\right)\left(x^4-1\right)\left(x^4+1\right)\)
\(=\left(x^8+2\right)\left(x^2-1\right)\left(x^2+1\right)\left(x^4+1\right)=\left(x^8+2\right)\left(x-1\right)\left(x+1\right)\left(x^2+1\right)\left(x^4+1\right)\)
e ) \(x^3-11x^2+30x=0\)
\(\Leftrightarrow x\left(x^2-11x+30\right)=0\)
\(\Leftrightarrow x\left[\left(x^2-5x\right)-\left(6x-30\right)\right]=0\)
\(\Leftrightarrow x\left[x\left(x-5\right)-6\left(x-5\right)\right]=0\)
\(\Leftrightarrow x\left(x-6\right)\left(x-5\right)=0\)
\(\Rightarrow x=0orx=5orx=6\) (or hoặc)
Vậy \(x\in\left\{0;5;6\right\}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
1,4x2.(5x3+2x-1)
=4x2.5x3+4x2.2x-4x2.1
20x5+8x3-4x2
2,4x3y2:x2
=4xy2
3,(15x2y3-10x3y3+6xy):5xy
15x2y3:5xy-10x3y3:5xy+6xy:5xy
3xy2-2x2y2+\(\dfrac{6}{5}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
1: \(=20x^5+8x^3-4x^2\)
2: \(=4xy^2\)
3: \(=3xy^2-2x^2y^2+\dfrac{6}{5}\)
4: \(=\dfrac{5x^3+10x^2+4x^2+8x+4x+8}{x+2}=5x^2+4x+4\)
5: \(=\dfrac{7}{2x}+\dfrac{11}{3y^2}=\dfrac{21y^2+22x}{6xy^2}\)
6: \(=\dfrac{4x^2-7x+3}{\left(4x-7\right)\left(x+2\right)}\)
7: \(=\dfrac{3x+3y-2x^3+2x^2y}{\left(x-y\right)\left(x+y\right)}\)
8: \(=\dfrac{1}{2}x^2y^2\left(4x^2-y^2\right)=2x^4y^2-\dfrac{1}{2}x^2y^4\)
9: \(=\left(x-\dfrac{1}{4}\right)\left(4x-1\right)=4\left(x-\dfrac{1}{4}\right)^2=4\left(x^2-\dfrac{1}{2}x+\dfrac{1}{16}\right)\)
\(=4x^2-2x+\dfrac{1}{4}\)
10: \(=\dfrac{3x^2+6-x}{x\left(2x+6\right)}=\dfrac{2x+6}{x\left(2x+6\right)}=\dfrac{1}{x}\)
11: \(=\dfrac{x+1}{2}-\dfrac{3}{x-1}\)
\(=\dfrac{x^2-7}{2\left(x-1\right)}\)
12: \(=\dfrac{x^2-xy}{\left(x-y\right)\left(x+y\right)}=\dfrac{x}{x+y}\)
15:=x^3-y^3+2
![](https://rs.olm.vn/images/avt/0.png?1311)
1: \(=20x^5+8x^3-4x^2\)
2: \(=4xy^2\)
3: \(=3xy^2-2x^2y^2+\dfrac{6}{5}\)
4: \(=\dfrac{5x^3+10x^2+4x^2+8x+4x+8}{x+2}=5x^2+4x+4\)
5: \(=\dfrac{7}{2x}+\dfrac{11}{3y^2}=\dfrac{21y^2+22x}{6xy^2}\)
6: \(=\dfrac{4x^2-7x+3}{\left(4x-7\right)\left(x+2\right)}\)
7: \(=\dfrac{3x+3y-2x^3+2x^2y}{\left(x-y\right)\left(x+y\right)}\)
8: \(=\dfrac{1}{2}x^2y^2\left(4x^2-y^2\right)=2x^4y^2-\dfrac{1}{2}x^2y^4\)
9: \(=\left(x-\dfrac{1}{4}\right)\left(4x-1\right)=4\left(x-\dfrac{1}{4}\right)^2=4\left(x^2-\dfrac{1}{2}x+\dfrac{1}{16}\right)\)
\(=4x^2-2x+\dfrac{1}{4}\)
10: \(=\dfrac{3x^2+6-x}{x\left(2x+6\right)}=\dfrac{2x+6}{x\left(2x+6\right)}=\dfrac{1}{x}\)
11: \(=\dfrac{x+1}{2}-\dfrac{3}{x-1}\)
\(=\dfrac{x^2-7}{2\left(x-1\right)}\)
12: \(=\dfrac{x^2-xy}{\left(x-y\right)\left(x+y\right)}=\dfrac{x}{x+y}\)
15:=x^3-y^3+2